Application of three-dimensional computed tomography imaging and reconstructive techniques in lung surgery: A mini-review - Vervoorn, Mats T.; Wulfse, Maaike; Mohamed Hoesein, Firdaus A. A.; Stellingwerf, Margriet; van der Kaaij, Niels P.; de Heer, Linda M. (Frontiers in Surgery, 2022)
Background Pulmonary surgery is an innovative discipline with increasing demands for minimally invasive techniques in complicated anatomical resections, warranting adequate preoperative imaging of relevant surgical anatomy to ensure safe and radical resection of target lesions. Over the recent years, the emergence of imaging techniques enabling three-dimensional reconstruction has exerted promising influence on pulmonary surgery, facilitating optimal surgical planning and easier identification of the spatial relationship between bronchovascular structures in the individual patient and aiding the safe resection of target pulmonary lesions. The goal of this mini-review is to provide an overview of three-dimensional computed tomography imaging within pulmonary surgery. Materials & Methods The authors performed a targeted qualitative review of the literature to identify current trends and to provide better understanding of three-dimensional reconstruction within the boundaries of pulmonary surgery. Results Three-dimensional reconstructive techniques can be used for resectability assessment, identification of surgically relevant interindividual anatomic variance and may improve perioperative outcomes. Discussion Three-dimensional reconstruction using computed tomography imaging improves surgical planning and there is evidence that it results in shorter operative times, less intraoperative blood loss and lower rates of surgical conversion, as it can be applied both pre- and intraoperatively.